Studying Stellar Rotation and Convection Theoretical Background and Seismic Diagnostics - Goupil, Mariejo; Belkacem, Kévin; Neiner, Coralie; Lignières, Francois; Green, John J. (Lecture Notes in Physics, 2013)
This volume synthesizes the results of work carried out by several international teams of the SIROCO (Seismology for Rotation and Convection) collaboration. It provides the theoretical background required to interpret the huge quantity of high-quality observational data recently provided by space experiments such as CoRoT and Kepler. Asteroseismology allows astrophysicists to test, to model and to understand stellar structure and evolution as never before. The chapters in this book address the two groups of topics summarized as "Stellar Rotation and Associated Seismology" as well as "Stellar Convection and Associated Seismology". The book offers the reader solid theoretical background knowledge and adapted seismic diagnostic techniques.